AN IMPROVED METHOD FOR THE FRET-BASED DETECTION OF CYCLIC NUCLEOTIDE SIGNALLING IN PRIMARY ADULT MOUSE CARDIOMYOCYTES. (21st November 2014) - Brescia, M; Lomas, O; Zaccolo, M
Abstract : Primary adult murine cardiomyocytes are an important tool for the investigation of cardiovascular physiology, especially with the development of transgenic mouse models. Fluorescence Resonance Energy Transfer (FRET) based probes have contributed greatly to the understanding of subcellular cAMP signalling. However, the transfer of genes encoding such probes into adult murine cardiomyocytes has proved difficult. Here we present a method for the effective adenovirus-mediated transduction of FRET biosensors that allow the investigation of cAMP signalling in adult murine cardiomyocytes in under 24 hours in culture. Furthermore we show that the contractility of adult murine cardiomyocytes in culture is not impaired by adenoviral gene transfer of FRET biosensors. Combined with a microscopy chamber perfusion system, that allows the removal of pharmacological agents such as specific inhibitors of phosphodiesterases (PDEs), this method allows the cost-effective, reproducible and rapid investigation of sub-cellular cAMP signalling and hence PDE activity in adult murine cardiomyocytes.